IPO Firms Subsequent Acquisition Activity and IPO Underperformance - Balapur, Ashish; Jessica, Mary (International Journal of Economics and Financial Issues, 2019)
We examine the IPO firm’s acquisition activity influence on the long-run performance of IPO during 1994-2015. We find that the IPO acquiring firms are generating positive abnormal returns for the first two years of going public and in the third, these firms generate negative abnormal returns, but they perform better than the non-acquiring IPO firms. We further investigate influence acquiring by introducing other factors which influence the performance of IPO, we find that the acquisition activity was not significant or weakly significant and beta values to be positive. We conclude that the investors are confident that the acquisition activity of IPO firms are value enhancing which otherwise believed. Keywords: IPO acquirer, BHAR, long-run performance. JEL Classifications: G24, G34 DOI: https://doi.org/10.32479/ijefi.8004